TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PERUSAHAAN PADA KSO PERTAMINA EP – SAMUDRA ENERGY BWPMERUAP DI KABUPATEN SAROLANGUN JAMBI: Corporate Social And Environmental Responsibility of the KSO Pertamina EP – Samudra Energy BWPMeruap in Sarolangun Regency, Jambi - Ifsaa Aaliya Saheera; Sri Bakti Yunari (Faculty of Law, Universitas Trisakti, 2025)
Article 74 of Law Number 40 of 2007 on Limited Liability Companies mandates that Companies that carry out their business activities in the field and/or related to natural resources are required to implement Social and Environmental Responsibility. The problems discussed in this study are how the implementation of Social and Environmental Responsibility is carried out by KSO Pertamina EP – Samudra Energy BWPMeruap and the obstacles in implementing the Social and Environmental Responsibility. The type of research used is normative legal research using secondary data and supported by primary data in the form of interview. The nature of this reserach is descriptive by conducting qualitative analysis and drawing conclusion deductively. Based on the result of the analysis of the Corporate Social and Environmental Responsibility carried out by KSO Pertamina EP – Samudra Energy BWPMeruap has been implemented but has not been optimal, due to legal and non-legal obstacle.